TAKWIL DALAM PERSPEKTIF ABDUL JABBAR (Sebuah Tawaran Hermeneutika al-Qur’an) - Moh. Alwy Amru Ghozali (Dialogia, 2016)
Abstract; Takwil is one of the ways to interpret Qur’an that is maintained and developed by Muktazilah. As that reason, this study focuses on Takwil initiated by Abdul Jabbar, the last Muktazilah figure. This study discussed theoretical background, object and method that are used by Abdul Jabbar in his takwil. Then, this researcher is summed up Abdul Jabbar Takwil is growing rapidly. As the reason, his takwil is in line with modern hermeneutics principals and Abdul Jabbar is one of interpreter that sees inherence between natural meaning and interpreter subjectivity.Keywords : Takwil, al-Qur’an, Abdul Jabbar